2016
DOI: 10.15740/has/ajss/11.1/159-165
|View full text |Cite
|
Sign up to set email alerts
|

Effect of organic manures on growth and yield of cashew cv. VENGURLA-4 under Konkan region of Maharashtra

Abstract: SummaryAn experiment on the effect of organic manures on growth and yield of cashew cv. . While, application of recommended dose of fertilizer + 10 kg FYM (T 8 -control) recorded significantly the maximum mean pooled yield of 4.8 kg/tree and superior over the rest of the treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This may be due to the effect of inorganic mulch in moisture conservation which may influence the nut size. This was earlier reported by Gajbhiye et al [17] in cashew cv. Vengurla-4 and Tiwari et al [18] in sapota.…”
Section: Effect On Nut Parameters Viz Nut Weight Nut Length and Nut B...supporting
confidence: 86%
“…This may be due to the effect of inorganic mulch in moisture conservation which may influence the nut size. This was earlier reported by Gajbhiye et al [17] in cashew cv. Vengurla-4 and Tiwari et al [18] in sapota.…”
Section: Effect On Nut Parameters Viz Nut Weight Nut Length and Nut B...supporting
confidence: 86%
“…Plants that had a high the number of flower showed high fruit production. It is supported by Gajbhiye et al (2016) who stated that the high and low production of cashew crops depends on the number of flowers produced. Therefore, to optimize fruit production, an increase in flowering is necessary.…”
Section: Resultsmentioning
confidence: 97%
“…Hence, there should be an appropriate nutrient supplementation to sustain the higher yield. Nitrogen fertilizer therefore, considered as a better option in increasing fertilizer use efficiency and providing a more balanced supply of nutrients (Hammed et al 2011;Gajbhiye et al 2016;Fernadez, 2001) [4,3,2] . Vanlauwe et al (2002) [8] reported that balanced application of major nutrient result into synergy and improved conservation and synchronization of nutrient release and crop.…”
Section: Resultsmentioning
confidence: 99%